Use of reacted and activated rubber in ultra-thin hot mixture asphalt overlay for wet-freeze climates. (20th September 2019) - Chen, Siyu; Gong, Fangyuan; Ge, Dongdong; You, Zhanping; Sousa, Jorge B.
Abstract: This study investigated the use of crumb rubber in hot mixture asphalt pavement. The two main objectives of this study were to enhance pavement performance in wet-freeze climates and mitigate the environmental issues caused by waste tires. In this study, a reacted and activated rubber modified gap-graded mixture, abbreviated as "RAR-ThinGap", was designed to improve performance in wet-freeze climates. The concepts behind this design were: an aggregate structure of stone-on-stone contact, a large asphalt film thickness, and elastic rubber fillers. Extensive laboratory tests and field noise measurement had been conducted to determine the properties of this mix. In general, the test results were favorable in regard to moisture damage resistance, low temperature cracking resistance, fatigue cracking resistance, rutting resistance, and noise reduction. The average fracture energy of the RAR-ThinGap mixture was at least four times higher than that of the control mixture at −24 °C. Higher fracture energy indicates an excellent ability to resist thermal cracking in wet-freeze climates. The RAR-ThinGap mix had a fatigue life over 50 times longer than that of the polymer modified SMA mixes or conventional dense-graded mixes. The stone-on-stone skeleton structure of the mixture enhanced the rutting resistance. After 20, 000 wheel passes, the average rut depth was 6.80 mm at a test temperature of 50 °C. This RAR-ThinGap mixture may provide an appropriate and environmental-friendly pavement designed for wet-freeze climates. Graphical abstract: Image 1008 Highlights: Reacted and activated rubber through dry process was used in asphalt pavement. Designed rubber modified mix with enhanced performance for wet-freeze climates. Showed features of stone-on-stone contact, thicker film, and elastic fillers. Displayed four to five times higher fracture energy than the control mix at −24 °C. Illustrated over 50 times longer fatigue life than the conventional asphalt mixes.